Acute effects of a thermogenic nutritional supplement on cycling time to exhaustion and muscular strength in college-aged men - Beck Travis W; Hoge Katherine M; Costa Pablo B; Ryan Eric D; Herda Trent J; Walter Ashley A; Stout Jeffery R; Cramer Joel T (Taylor & Francis Group, 2009)
Abstract Background The purpose of the present study was to examine the acute effects of a thermogenic nutritional supplement containing caffeine, capsaicin, bioperine, and niacin on muscular strength and endurance performance. Methods Twenty recreationally-active men (mean ± SD age = 21.5 ± 1.4 years; stature = 178.2 ± 6.3 cm; mass = 76.5 ± 9.9 kg; VO2 PEAK = 3.05 ± 0.59 L/min-1) volunteered to participate in this randomized, double-blinded, placebo-controlled, cross-over study. All testing took place over a three-week period, with each of the 3 laboratory visits separated by 7 days (± 2 hours). During the initial visit, a graded exercise test was performed on a Lode Corival cycle ergometer (Lode, Groningen, Netherlands) until exhaustion (increase of 25 W every 2 min) to determine the maximum power output (W) at the VO2 PEAK (Parvo Medics TrueOne® 2400 Metabolic Measurement System, Sandy, Utah). In addition, one-repetition maximum (1-RM) strength was assessed using the bench press (BP) and leg press (LP) exercises. During visits 2 and 3, the subjects were asked to consume a capsule containing either the active supplement (200 mg caffeine, 33.34 mg capsaicin, 5 mg bioperine, and 20 mg niacin) or the placebo (175 mg of calcium carbonate, 160 mg of microcrystalline cellulose, 5 mg of stearic acid, and 5 mg of magnesium stearate in an identical capsule) 30 min prior to the testing. Testing included a time-to-exhaustion (TTE) ride on a cycle ergometer at 80% of the previously-determined power output at VO2 PEAK followed by 1-RM LP and BP tests. Results There were no differences (p > 0.05) between the active and placebo trials for BP, LP, or TTE. However, for the BP and LP scores, the baseline values (visit 1) were less than the values recorded during visits 2 and 3 (p ≤ 0.05). Conclusion Our findings indicated that the active supplement containing caffeine, capsaicin, bioperine, and niacin did not alter muscular strength or cycling endurance when compared to a placebo trial. The lack of increases in BP and LP strength and cycle ergometry endurance elicited by this supplement may have been related to the relatively small dose of caffeine, the high intensity of exercise, the untrained status of the participants, and/or the potential for caffeine and capsaicin to increase carbohydrate oxidation.